Analisis Sentimen Masyarakat Terhadap Kebijakan Campuran BBM E10 Menggunakan Metode Naive Bayes - Suci Intania Indah; Hannie; Ahmad Khusaeri (Universitas Lampung, 2026)
The mandatory policy of 10% ethanol blending in fuel oil (BBM E10), announced in October 2025, triggered a wide range of responses from the Indonesian public, particularly on the X social media platform. This study aims to analyze the sentiment of Platform X users towards the BBM E10 policy and evaluate the performance of a classification model built using the Multinomial Naïve Bayes algorithm. The method applied is Knowledge Discovery in Database (KDD), encompassing data selection, preprocessing, transformation, data mining, and evaluation stages. Data was collected through crawling using the Twitter API with keywords